(untitled) (Analysis of International Sciences, 2024)
This article explores the translation of reality as one of the urgent problems in literary translation. It delves into the challenges faced by translators when conveying the complex and multifaceted realities portrayed in literary works. The article discusses the cultural sensitivity required, the difficulties in translating idiomatic expressions and historical accuracy, and the need for stylistic adaptation. It also highlights the importance of reader reception and intertextuality in conveying realities effectively. The article emphasizes the role of translators in faithfully representing and bridging the cultural realities between source and target languages.